Relationship between Nutritional Status and Incidence of Respiratory Tract Pneumonia Lower Respiratory Disorders in Toddlers in the Region Work Health Center - Srifitayani, Nur Rahma; Nurmiati, Nurmiati; Jannah, Raudatul; Wahyuni, Tri (International Journal of Health Sciences, 2025)
Pneumonia is one of the reason main mortality in children under five, especially in developing countries. Nutritional status toddler be one of factor risk important that can influence vulnerability to infection channel breathing below. Research this aiming for know connection between nutritional status with respiratory tract pneumonia incident breathing lower specifically for toddlers in the work area health center. Research methods used is descriptive analytic with cross sectional approach. Samples were taken purposively sampling 80 toddlers aged 12–59 months. Data were collected through interview use questionnaire and measurement of nutritional status based on indicator weight according to age (BW/A). Research results show that part big toddler with nutritional status bad and lacking having pneumonia. Statistical test show there is significant relationship​ between nutritional status with incidence of pneumonia in toddlers (p < 0.05). It was concluded that nutritional status play a role important in the incidence of pneumonia in toddlers. Therefore that, intervention nutrition and promotion health need improved for lower number pneumonia incident.